2022
DOI: 10.1177/23779608221139080
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Satisfaction and Self-Confidence Levels After Their Simulation Experience

Abstract: Background Nursing students should be well prepared before going to clinical setting as they provide direct care to patient. Simulation gives the learners the opportunity to be active learners who practice, train, and give a reflection on a specific experience. Objective To obtain an understanding of the human patient simulation experience and nursing students’ perceptions of satisfaction and self-confidence. Method Cross-sectional, descriptive design was undertaken. Using purposive sampling, 273 nursing stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
3
5
0
Order By: Relevance
“…Likewise, the results obtained in Fatih's research (2019) showed that there was a significant difference in the level of student satisfaction after and before using the simulation learning method. In line with previous research conducted by Alharbi (2022) which obtained research results that simulation is effective in increasing satisfaction and self-confidence of nursing students in preparing skills in hospitals (H Al Fatih et al, 2019;K Alharbi, 2022). Meanwhile, according to Mystakidis (2022) in his research also argues, in addition to obtaining benefits in using VR, students also have the opportunity to get other disadvantages, namely the privacy data security system which is still often reported due to the activities of using this metaverse product which is still too broad and free, health and safety guarantees for VR users, physical well-being, opportunities for injury due to fatigue in the neck and head, to other physical symptoms such as nausea and dizziness.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, the results obtained in Fatih's research (2019) showed that there was a significant difference in the level of student satisfaction after and before using the simulation learning method. In line with previous research conducted by Alharbi (2022) which obtained research results that simulation is effective in increasing satisfaction and self-confidence of nursing students in preparing skills in hospitals (H Al Fatih et al, 2019;K Alharbi, 2022). Meanwhile, according to Mystakidis (2022) in his research also argues, in addition to obtaining benefits in using VR, students also have the opportunity to get other disadvantages, namely the privacy data security system which is still often reported due to the activities of using this metaverse product which is still too broad and free, health and safety guarantees for VR users, physical well-being, opportunities for injury due to fatigue in the neck and head, to other physical symptoms such as nausea and dizziness.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the emphasis on satisfaction and suggestions in the content analysis indicated that the training program was well received and that participants valued the opportunity to provide feedback for continuous improvement. These findings were consistent with earlier studies [43,44], which provided further evidence supporting the effectiveness of hybrid simulation as an effective educational and training tool. Further research is needed to explore the optimal use of simulation as a teaching strategy and to identify the factors that contribute to its success in promoting the development of nursing students' clinical competence.…”
Section: Discussionsupporting
confidence: 92%
“…There was little agreement in the literature about this point although several studies have revealed how nursing students’ levels of confidence change during their academic careers ( Alharbi & Alharbi, 2022 ; Makarem et al, 2019 ; Post University Blog, 2022 ; Twidwell et al, 2022 ). Sasat et al (2002) for example analyzed several facets of nursing student self-confidence over the course of three years and found no correlation between self-confidence and year of study in the nursing program under consideration.…”
Section: Discussionmentioning
confidence: 99%